Urban funding regularization, environmental disasters, civil defense and mining: braskem and gema salt extraction in Maceió - Bittencourt, Márcio Teixeira; de Toledo, Peter Mann; Rocha, Gilberto de Miranda (Seven Editora, 2023)
Description and Comments on the Legislation in force and its effectiveness in public policies, one item dedicated to Land Regularization, the other to Environmental Disasters and Civil Defense, and the third to Mining. The case study will be about Braskem and the extraction of rock salt in Maceió - AL. In the final considerations, the importance of compatibility between legislation and public policies is highlighted in the three themes Urban Land Regularization, Environmental Disasters, and Mining. DOI: https://doi.org/10.56238/devopinterscie-060